SPE Annual Technical Conference and Exhibition 2017
DOI: 10.2118/187412-ms
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Non-Uniform Production Rate Distribution of Multi-Fractured Horizontal Well Through Pressure Transient Analysis: Model and Case Study

Abstract: The severe decline of oil production has been observed in many multi-fractured horizontal wells (MFHW) within only one or two years. It is thus essential to determine production rate distribution of MFHW for improving oil production. However, available pressure-transient analysis (PTA) models of MFHW hardly consider the effect of non-uniform production rate distribution of both horizontal sections and hydraulic fractures on pressure-transient response, which may lead to erroneous results. This p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…In fact, PLT results have demonstrated that the production profile is non-uniform [12,48,49] as shown in Figure 1. Although He et al and Qin et al [49][50][51] have presented PTA models of to analyze the effects of non-uniform production on pressure transient characteristics, the well testing interpretation is limited since is hard to reflect the information for a large region with testing data due to the low permeability in tight formations and short testing time. Qin et al discussed the rate transient response of a multi-segment horizontal well with non-uniform production distribution along horizontal wellbores [52].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, PLT results have demonstrated that the production profile is non-uniform [12,48,49] as shown in Figure 1. Although He et al and Qin et al [49][50][51] have presented PTA models of to analyze the effects of non-uniform production on pressure transient characteristics, the well testing interpretation is limited since is hard to reflect the information for a large region with testing data due to the low permeability in tight formations and short testing time. Qin et al discussed the rate transient response of a multi-segment horizontal well with non-uniform production distribution along horizontal wellbores [52].…”
Section: Introductionmentioning
confidence: 99%
“…He et al [37] proposed a method for estimating malfunctioning horizontal wellbore through bottom hole pressure data. Qin et al [38] developed novel approach to evaluate nonuniform production distribution of multifractured horizontal wellbore based on PTA. During past years, although plenty of work has been developed for PTA of horizontal wells and multifractured horizontal wells with multiple sections [39][40][41][42][43], rate decline analysis of HWMS is still rarely documented.…”
Section: Introductionmentioning
confidence: 99%
“…Aibazarov et al [20] described how to determine the downhole fluid flow path and further to optimize water shut-off operations by using integrating data from spectral noise logging tools and multisensor production logging. Over the past few years, many researchers pinpointed water entry intervals through production logging [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. On the other hand, another monitoring system can provide vital data (e.g., pressure and temperature) for waterinflux detection.…”
Section: Introductionmentioning
confidence: 99%